The significant factors causing delay of building construction projects in Malaysia. - Alaghbari, Wa'el; A. Kadir, Mohd. Razali; Salim, Azizah; Mustafa Kamal, Ernawati (Emerald, 2007)
Purpose – The paper seeks to identify the major factors causing delay in building construction projects in Malaysia.